IMPLEMENTASI LMS MOODLE UNTUK E-LEARNING SD MUHAMMADIYAH MAESAN DAN SD MUHAMMADIYAH BANGERAN, YOGYAKARTA - Fajrin, Hanifah Rahmi; Widadi, Sigit; Raharja, Arif Budi (Universitas Muhammadiyah Tapanuli Selatan, 2021)
Generally, schools in remote areas, in this case SD Muhammadiyah Maesan and SD Muhammadiyah Bangeran have few students, this could be due to several factors related to learning technology, namely: teacher competence in using ICT devices for learning is inadequate, elementary schools do not yet have software as a forum for digital learning content that can be a medium for interaction of teaching and learning activities between teachers and students via the internet, ICT infrastructure in elementary schools is not sufficient for learning. Therefore, the community service team implemented a Moodle learning management system (LMS) platform for learning in both schools. With this e learning platform, it can make it easier for teachers or teaching staff to create IT / e learning-based teaching material content. The teachers are taught the process of installing, dressing and maintaining the devices. After the implementation of community service, SD Muhammadiyah Maesan and SD Muhammadiyah Bangeran can use e-learning / moodle cloud in managing the subjects to be taught.